Low Temperature, Digital Control, Fast Synthesis of 2-D BNNSs and Their Application for Deep UV Detectors. Issue 1726 (20th July 2015) - Aldalbahi, Ali; Yang, Renyauan; Li, Eric Yiming; Sajjad, Muhammad; Chen, Yihau; Feng, Peter
ABSTRACT: This paper reports low temperature, digital control, fast synthesis of high-quality boron nitride nanosheets (BNNSs) and their electronic device application. Raman scattering spectroscopy, X-ray diffraction (XRD), Transmission electron microscopy (TEM) are used to characterize the BNNSs. With the synthesized various BNNSs, two prototypic types of deep UV photodetectors have been fabricated, and sensitivity, response and recovery times, as well as repeatability have been characterized. Effects of period and thickness of BNNSs on the properties of prototypic photodetectors are also discussed.